Bio-ethanol production by marine yeasts isolated from coastal mangrove sediment - Senthilraja, K. Kathiresan, K. Saravanakumar, P. (International Multidisciplinary Research Journal, 2011)
This study analyzed ethanol production by 10 marine strains of yeasts, isolated from mangrove sediments. Of the species tested, Pichia salcaria exhibited the maximum ethanol production of 12.3±3.1 g/l. This was further studied in the culture filtrate supplemented with different concentrations (0.01, 0.1, 1, 2 and 4% w/v) of sawdust as substrate that was pre-processed with phosphoric acid, and then incubated for different durations (24,48,72, 96 and 120 h). The ethanol production by P. salcaria was found maximum (26.2±8.9 g/l) in 72 hours of fermentation in the culture broth supplemented with 2% sawdust that was preprocessed with dilute phosphoric acid. This condition of fermentation was found coincided with high activity cell ase in the cul ure broth, which also revealed a single prominent protein band of 68 kDa molecular weight, similar to cellulase. The study proved the efficiency of marine P. salcaria in bioethanol production.